Menakar Sistem Jual Beli Ikan Gelondongan Dalam Pandangan Hukum Islam - Suaidi Suaidi (Al Yazidiy Jurnal Sosial Humaniora dan Pendidikan, 2023)
This study aims to determine the status of Islamic law regarding the system of buying and selling fish logs which has become the culture of the Gersik area, the source of income in this area is mostly from fish ponds. Buying and selling is part of the types of transactions taught by Islam, even the type of business that is prioritized and regulated specifically is buying and selling. The principle of commerce in the buying and selling system in Islamic law must be sterile from mixing it with interest which is punishable by usury. Businesses that contain usury are punished as a source of poverty both in this world and in the hereafter. The sale and purchase of logs, which has become an integral part of people's lives as a main source of income, requires an explanation of its legal status. And, it is very interesting to study it through research so that there are no more doubts about its legal status.